Eligibility of Natural Disaster Victims as Zakat Recipients: An Analysis From a Shariah Perspective - Muhammad Azhad Al-Bohari; Nurul Ain Chua (USIM Press, 2025)
Malaysia has witnessed an increasing frequency of natural disasters, particularly floods and landslides, which have had devastating effects on communities across the nation. While zakat distribution in some states primarily focuses on the faqīr and miskīn categories, other eligible asnaf, such as al-ghārimūn (debtors), Ibn Sabīl (stranded travelers), and Muallaf Qulūbuhum (those whose hearts are inclined towards Islam), remain underutilized in disaster relief efforts. This limited approach may hinder the full potential of zakat in alleviating hardship among disaster victims. This study examines the potential expansion of zakat eligibility to these additional categories, in line with classical and contemporary Shariah discussions. Using a qualitative research approach, including library research and descriptive analysis, this paper explores the role of zakat as an effective mechanism for disaster relief. The findings highlight the necessity of a more inclusive zakat distribution model that accommodates various asnaf to ensure comprehensive and targeted support for victims of natural calamities. By integrating these additional asnaf into zakat disbursement policies, zakat institutions can enhance their humanitarian role and improve the efficiency of financial aid distribution. Moreover, a structured and well-coordinated zakat allocation system will not only optimize disaster response efforts but also strengthen public awareness regarding zakat’s role in social welfare. This study advocates for a more dynamic and adaptive zakat framework that maximizes the impact of zakat funds in supporting affected communities, ensuring that assistance reaches those most in need in a timely and effective manner.